2006
DOI: 10.1111/j.1530-0277.2006.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Alcoholics Anonymous Membership, and Homicide Mortality Rates in Ontario 1968 to 1991

Abstract: These data provide important support for the selective disinhibition model and confirm important relationships between per capita consumption measures and homicide mortality rates, especially among males, seen in other studies. Additionally, the results for AA membership rates are consistent with the hypothesis that AA membership and treatment for misuse of alcohol can exert beneficial effects observable at the population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
3
29
0
1
Order By: Relevance
“…The incidence of alcohol-positive toxicology tests from homicide victims described in the literature is variable, ranging from 17% to 63%. 5,24,25 In our study, the victims' toxicology tests were positive for alcohol in 49%.…”
Section: Mechanism Of Deathmentioning
confidence: 87%
See 1 more Smart Citation
“…The incidence of alcohol-positive toxicology tests from homicide victims described in the literature is variable, ranging from 17% to 63%. 5,24,25 In our study, the victims' toxicology tests were positive for alcohol in 49%.…”
Section: Mechanism Of Deathmentioning
confidence: 87%
“…Defense wounds are not uncommon upon the victims of homicide, with typical locations such as forearm and hands, being valuable evidence in homicidal deaths. 23 A large amount of research has demonstrated a strong link between alcohol use and violence 24 and it has been described as an important factor in violent interactions that culminate in homicide. 25 Besides facilitating conflicts and increasing the potential for violent behaviours by the perpetrator, it also weakens and disorientates the victim, thus reducing the discerning and self-defence capabilities, making them an "easy target" for assaults.…”
Section: Mechanism Of Deathmentioning
confidence: 99%
“…violence between dealers). For the purposes of this review, these risk factors might be divided broadly into two groups: proximal (pharmacological) and distal (lifestyle-related, including 'economic compulsive' and 'systemic' violence) [5][6][7][8][9][10][11][12][13]. Proximal factors relate, essentially, to the acute psychotropic effects of particular drugs.…”
Section: Substance Use and Homicide Riskmentioning
confidence: 99%
“…Although the extent to which this relationship is causal has been debated (Parker and Auerhahn, 1998), there is some evidence that receipt of help may reduce criminal outcomes among individuals with AUDs. For example, in a longitudinal study of a Canadian population-based sample, Mann et al (2006) reported a negative relationship between AA membership and homicide mortality rates in men (but not in women). Moreover, individuals in treatment for drug addiction, or for substance use problems more generally, have been shown to improve on legal outcomes using either 12-step or formal interventions (McLellan et al, 1986;Ouimette et al, 1997Ouimette et al, , 1998.…”
Section: Change In Impulsivity Participation In Aa and Treatment Anmentioning
confidence: 99%